MANAGEMENT OF INNOVATION ACTIVITIES OF TRADE ENTERPRISES (INNOVATIVE ECONOMY, 2024)
Dekaliuk O.V., Nianko V.M., Ploskonos N.V. MANAGEMENT OF INNOVATION ACTIVITIES OF TRADE ENTERPRISESPurpose. The aim of the article is to consider the components of innovation processes and factors of resistance to innovations of trade enterprises.Methodology of research. The study uses a systematic approach that reflects the role of innovation processes in the activities of trade enterprises. The following scientific methods were used in the research process to achieve this goal: scientific abstraction, deduction and induction – to formulate a scientific hypothesis of work, laws and principles; abstract and logical - to make theoretical generalisations, substantiate the research methodology, formulate conclusions; monographic - to study the innovation processes of trade enterprises; method of system analysis for theoretical generalisations of innovation processes of trade enterprises, etc.Findings. The problems and prospects for the development of innovative activities of trade enterprises in Ukraine are considered, which is due to the rapid digitalisation of society, business and government. The use of innovations in trade enterprises is studied. The role and place of implementation of innovation policy at the enterprise in the development of plans and programmes for innovative changes, consistent understanding of the implementation of the innovation development project, and monitoring its progress in the process of implementation are clarified. The importance of a unified innovation policy for all functional and production units of a trading enterprise is substantiated.Originality. The methodology of expert assessment of factors that cause resistance to innovation in the divisions of a trade enterprise has been further developed. An expert assessment was carried out and the factors that have a decisive influence on resistance to innovation in trade enterprises were identified.Practical value. Based on the results of the study, a system of indicators for expert evaluation of factors that cause resistance to innovation in the divisions of a trade enterprise was substantiated.Key words: management, trade enterprise, innovation, expert assessment, resistance.
Keywords: management; trade enterprise; innovation; expert assessment; resistance.